(untitled) (Journal of Pathology of Nepal, 2012)
Background: Gastric carcinoma is one of the leading causes of cancer deaths worldwide, with a mortality rate directly related to the stage at diagnosis. Endoscopic biopsy and cytology are well established techniques for the diagnosis of carcinoma of stomach. Materials and Methods: This study was conducted on 50 patients, suspected of gastric cancer on endoscopy, during a period of 18 months (October 2010 to March 2012). Endoscopic biopsy and touch smear cytology were evaluated. Biopsy was considered gold standard for final diagnosis. Results: A total of 50 cases were included out of which 36 were malignant and 14 cases were benign. Cytology was able to diagnose 33 out of 36 malignant cases. Of 17 cases which were diagnosed as benign on cytology, 3 cases turned out to be malignant on biopsy. The sensitivity and specificity of touch smear cytology are 91.6% and 100% respectively. Conclusion: Touch smear cytology is a useful adjunct in the diagnosis of gastric carcinoma and should be considered a routine method along with biopsy. Journal of Pathology of Nepal (2012) Vol. 2, 282-284 DOI: http://dx.doi.org/10.3126/jpn.v2i4.6878